Using Intersectionality to Identify Gendered Barriers to Health-Seeking for Febrile Illness in Agro-Pastoralist Settings in Tanzania - Barasa, Violet; Virhia, Jennika (Frontiers in Global Women's Health, 2022)
Background Research has shown that gender is a significant determinant of health-seeking behavior around the world. Gender power relations and lay etiologies of illness can influence the distribution of household resources, including for healthcare. In some rural settings in Africa, gender intersects with multiple forms of health inequities, from proximal socio-cultural factors to more “upstream” or distal health system determinants which can amplify barriers to health-seeking for specific groups in specific contexts. Aim We used an intersectionality approach to determine how women in particular, experience gendered barriers to accessing healthcare among Maa and non-Maa speaking agro-pastoralists in northern Tanzania. We also explored lay etiologies of febrile illness, perceptions of health providers and rural health-seeking behavior in order to identify the most common barriers to accessing healthcare in these settings. Methods Mixed method ethnographic approaches were used to collect data between 2016 and 2018 from four Maa-speaking and two Swahili-speaking agro-pastoralist villages in northern Tanzania. Maa-speaking villages were based in Naiti, Monduli district while non-Maa speaking villages were selected from Msitu in Babati district. Data on health seeking behaviors was collected through semi-structured questionnaires, in-depth interviews, focus group discussions, and home and facility-based participant observation. Findings The results primarily focus on the qualitative outcomes of both studies. We found that febrile illness was locally categorized across a spectrum of severity ranging from normal and expected illness to serious illness that required hospital treatment. Remedial actions taken to treat febrile illness included attending local health facilities, obtaining medicines from drug sellers and use of herbal remedies. We found barriers to health-seeking played out at different scales, from the health system, community (inter-household decision making) and household (intra-household decision making). Gender-based barriers at the household had a profound effect on health-seeking. Younger married women delayed seeking healthcare the most, as they often had to negotiate health-seeking with husbands and extended family members, including co-wives and mothers-in-law who make the majority of health-related decisions. Conclusion An intersectional approach enabled us to gain a nuanced understanding of determinants of health-seeking behavior beyond the commonly assumed barriers such lack of public health infrastructure. We propose tapping into the potential of senior older women involved in local therapy-management groups, to explore gender-transformative approaches to health-seeking, including tackling gender-based barriers at the community level. While these social factors are important, ultimately, improving the public health infrastructure in these settings is a first step toward addressing structural determinants of treatment-seeking.